2013
DOI: 10.7567/jjap.52.11ng02
|View full text |Cite
|
Sign up to set email alerts
|

InGaN-Based Light-Emitting Diodes Fabricated on Nano Patterned Sapphire Substrates with Pillar Height of More than 600 nm by Nanoimprint Lithography

Abstract: GaN-based light-emitting diodes (LEDs) were fabricated on nano patterned sapphire substrates (nano-PSSs) by nanoimprint (NIP) lithography. A nano-PSS with a pillar height of more than 600 nm was achieved. The surface emission of the LEDs was strongly affected by pillar height, and the surface emission intensity was highest at a pillar height of 250 nm. In contrast, the external quantum efficiency of the LEDs on the nano-PSSs with diameters of 100 and 450 nm was approximately 30% higher than that on a flat sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…12a). 146 It was found that pattern height affected the surface emission of LEDs and highest emission intensity was obtained at a pillar height of 250 nm. The utilization of such PSS improved LEE and efficiency droop of LEDs, indicating the advantage of PSS over FSS (Fig.…”
Section: Influence Of Structural Parameters Of Pss On Led Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…12a). 146 It was found that pattern height affected the surface emission of LEDs and highest emission intensity was obtained at a pillar height of 250 nm. The utilization of such PSS improved LEE and efficiency droop of LEDs, indicating the advantage of PSS over FSS (Fig.…”
Section: Influence Of Structural Parameters Of Pss On Led Propertiesmentioning
confidence: 99%
“…(b) EQEs of LED chips on nano-PSSs as a function of injection current. Reproduced with permission 146. Copyright 2013, Institute of Physics Publishing.…”
mentioning
confidence: 99%
“…While the device performance is enhanced significantly by the patterned sapphire, the pattern shapes are still random. NIL can be applied to fabricate sapphire substrates with designed textures [55][56][57]. For example, with the same procedure in the conventional NIL, the patterns were first transferred by pressing a flexible polyvinylchloride (PVC) stamp into the UV curable resist along with UV light exposure [55].…”
Section: Nil Involving Dry Etching Processmentioning
confidence: 99%
“…The patterned sapphire can enhance the luminescence efficiency of LEDs [55,56]. For example, a GaN based LED on a nanometer-scaled patterned sapphire substrate exhibited a stronger and sharper photoluminescence (PL) emission peak than that of the unpatterned LED [55].…”
Section: Applications Of Ceramic Nanostructures Prepared By Nilmentioning
confidence: 99%
“…Yet, only a few approaches have been applied to form nanoscale patterns, especially for the one with a well-ordered arrangement [8]. Due to high cost and low throughput of these complex nanofabrication approaches, nanoscale PSS could not be implemented in commercial products [12]. For this reason, a potentially alternative approach to form nanoscale pattern by the use of self-organized anodized aluminum oxide (AAO) film is studied.…”
Section: Introductionmentioning
confidence: 99%